2008
DOI: 10.1080/13880200701734661
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Activities of Commercial Rosemary Oils (Rosmarinus officinalis.) Against Larvae ofPseudaletia unipuncta. andTrichoplusia ni. in Relation to Their Chemical Compositions

Abstract: Rosemary [Rosmarinus officinalis L. (Lamiaceae)] essential oil has insecticidal properties and is the active ingredient in a number of commercial insecticides. Like other plant essential oils, the chemical composition of rosemary oil can vary based on genotype, geography, climate, and method of preparation. This study explored the relationship between chemical composition and insecticidal activity of 10 commercial samples of rosemary oil, based on laboratory bioassays with two agricultural pests, the armyworm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(76 citation statements)
references
References 17 publications
4
65
0
7
Order By: Relevance
“…In terms of the synergistic effects of the combination of terpineoids with 1,8-cineole, our findings are similar to those of Singh et al (2009). These additive and synergistic effects of binary mixtures against lepidopterans could be attributed to their ability to prevent habituation of the olfactory response in the larval and adult stages (Akhtar and Isman, 2003;Koul et al, 2003;Isman et al, 2008;Singh et al, 2009). For this reason, MEC-spice oleoresins composed of binary mixtures merit further study as potential deterrents or repellents for other lepidopteran pests.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In terms of the synergistic effects of the combination of terpineoids with 1,8-cineole, our findings are similar to those of Singh et al (2009). These additive and synergistic effects of binary mixtures against lepidopterans could be attributed to their ability to prevent habituation of the olfactory response in the larval and adult stages (Akhtar and Isman, 2003;Koul et al, 2003;Isman et al, 2008;Singh et al, 2009). For this reason, MEC-spice oleoresins composed of binary mixtures merit further study as potential deterrents or repellents for other lepidopteran pests.…”
Section: Discussionsupporting
confidence: 75%
“…Generally, the combined effect of binary mixtures of essential oil constituents was found to be greater than that of individual compounds owing to their additive and synergistic effects against lepidopterans (Isman et al, 2008;Singh et al, 2009). For example, the binary mixture of 1,8-cineole with α-terpinyl acetate in MEC-C formulation was more deterrent than MEC-E formulation containing 1,8-cineole alone against codling moth larvae and adults.…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesized that the volatile compounds present in rosemary may have repellent effects to vegetable aphids. Some studies have shown that rosemary essential oil has insecticidal properties [13,14] . Isman et al [13] studied the insecticidal effects of rosemary oils on larvae of the moths Pseudaletia unipuncta and Trichoplusia ni in relation to the oils' chemical compositions.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that rosemary essential oil has insecticidal properties [13,14] . Isman et al [13] studied the insecticidal effects of rosemary oils on larvae of the moths Pseudaletia unipuncta and Trichoplusia ni in relation to the oils' chemical compositions. Hori et al [14] found that rosemary oil as well as thyme oil strongly repelled the aphid Myzus persicae (Sulzer), and rosemary oil has been shown to repel other aphid species such as Aphis gossypii Glover, Macrosiphum euphorbiae [15] ,…”
Section: Introductionmentioning
confidence: 99%
“…1,8-cineole was the second best effective compound against C. partellus and this compound is shown to have potential against other lepidopterans like S. litura, Psedaletia unipuncta and Trichoplusia ni (Hummelbrunner and Isman 2001;Isman et al 2008). Linalool was significantly similar to thymol and 1,8-cineole in its activity against C. partellus and is known as a potent, efficacious compound against mosquitoes (Traboulsi et al 2002(Traboulsi et al , 2005Cheng et al 2009) and fruit flies ), however, moderate activity has been reported against red bud borer, Resseliella oculiperda (van Tol et al 2007).…”
Section: Discussionmentioning
confidence: 99%